Factors Influencing Residents' Willingness to Contract With General Practitioners in Guangzhou, China, During the GP Policy Trial Phase: A Cross-Sectional Study Based on Andersen's Behavioral Model of Health Services Use - Zhongqi Liu MB; Yawen Tan MB; Haiqing Liang MB; Yijun Gu MB; Xiaowen Wang MB; Yuantao Hao PhD; Jing Gu PhD; Chun Hao PhD (SAGE Publishing, 2019)
This study aimed to investigate the current contract rate and residents' willingness to contract with general practitioner (GP) services in Guangzhou, China, during the policy trial phase, and also to explore the association of behavior contract and contract willingness with variables based on Andersen's Behavioral Model of Health Services Use (ABM). In total, 160 residents from community health centers (CHCs) and 202 residents from hospitals were recruited in this study. The outcome variables were behavior contract and contract willingness. Based on the framework of ABM, independent variables were categorized as predisposing factors, enabling factors, need factors, and CHC service utilization experiences. Univariate and multivariate logistic regression analysis models were applied to explore the associated factors. Out of 362 participants, 14.4% had contracted with GP services. For those who had not contracted with GP services, only 16.4% (51 out of 310) claimed they were willing to do so. The contract rate for community-based participants was significantly higher than that for hospital-based participants. Major reasons for not choosing to contract were perceiving no benefit from the service and concerns about the quality of CHCs. Community health center experiences and satisfaction were significantly associated with contracting among hospital-based participants. A need factor (diagnosed with hypertension or diabetes) and CHC service utilization experiences (have gotten services from the same doctor in CHCs) were significantly associated with contract willingness among CHC-based participants. Intervention to improve awareness of GP services may help to promote this service. Different intervention strategies should be used for varying resident populations.